Differences in Syphilis Incidence Using a Laboratory Algorithm in People With and Without HIV in an 11-Year Nationwide Cohort Study. (22nd January 2021) - Maier, Marissa M; Gylys-Colwell, Ina; Lowy, Elliott; Borgerding, Joleen; Van Epps, Puja; Ohl, Michael; Hauser, Ronald G; Chartier, Maggie; Beste, Lauren
Abstract: Background: To measure the incidence of syphilis diagnoses among people with HIV vs those without HIV in a national multiyear retrospective cohort. Methods: Treponemal and nontreponemal tests, HIV status, and demographic data were identified among all individuals receiving Veterans Health Administration (VHA) care between January 1, 2009, and December 31, 2019. Syphilis testing rates and incident syphilis diagnoses as defined by a laboratory algorithm were stratified by HIV status. Results: Syphilis was diagnosed in 1.2% (n = 2283) of 194 322 tested individuals in VHA care in 2019. Among individuals with HIV tested for syphilis, 6.1% met criteria for syphilis compared with 0.7% without HIV. Syphilis incidence in 2019 was 35/100 000, a 17% increase from 2009 (30/100 000). In 2019, syphilis incidence was 3381 per 100 000 persons among individuals with HIV and 19 per 100 000 in those without HIV. Conclusions: Using a laboratory-based diagnostic algorithm, a 178-fold difference in syphilis incidence was observed between individuals with and without HIV in 2019. US syphilis incidence data that incorporate HIV status are needed. Interventions to monitor and prevent sexually transmitted infections should address the role of HIV status.